The role of the gastrointestinal tract in the pathogenesis of rheumatic diseases. Issue 5 (October 2016) - Ciccia, Francesco; Ferrante, Angelo; Guggino, Giuliana; Triolo, Giovanni
Abstract: Dysregulation of the intestinal epithelial barrier in genetically susceptible individuals may lead to both intestinal and extraintestinal autoimmune disorders. There is emerging literature on the role of microbiota changes in the pathogenesis of systemic rheumatic diseases such as rheumatoid arthritis, spondyloarthropathies, and connective tissue diseases. Although the role of the gastrointestinal tract in the pathogenesis of spondyloartropathies is well defined and many studies underline the importance of gastrointestinal inflammation in modulating local and systemic inflammation, the data are inconclusive regarding the effect of dysbiosis on rheumatoid arthritis and connective tissue diseases. This review aims to summarize current data on the role of the gastrointestinal involvement and intestinal microbiota in the pathogenesis of systemic rheumatic disease.